Antibiotic Susceptibility Pattern of Acinetobacter baumannii in Clinical Isolates of Tertiary Care Hospital, Rawalpindi - Ali, Usman; Kaleem, Fatima; Aftab, Irum; Abbasi, Shahid Ahmad; Malik, Sara Naseem; Wali, Nadia (Infectious Diseases Journal of Pakistan, 2023)
Background: Acinetobacter baumannii is an important cause of nosocomial infections. It is developing resistance to many drugs including carbapenems, leading to concerns of increased mortality and cost of illness. The objective of the study was to find antibiotic susceptibility pattern of Acinetobacter baumannii. Methods: A descriptive study was conducted in the Microbiology Department, Fauji Foundation Hospital, Rawalpindi, from January 2015 to August 2015. A total of 146 isolates from various clinical specimens were identified as Acinetobacter baumannii using standard microbiological techniques and the antimicrobial susceptibility was carried out by using Kirby- Bauer disc diffusion technique as recommended by Clinical and Laboratory Standards Institute (CLSI). Frequency and percentages were calculated using SPSS (Version 21). Results: Of total 146 isolates, were obtained from clinical specimens of endo-tracheal tube, pus, blood, sputum, endo-bronchial fluid, cannula, urine, cerebrospinal fluid and high vaginal swab. 47.2% isolated were obtained from Intensive care unit and 52.7% were obtained from other wards/OPD of hospital. Resistance to tigecycline was 56.7%, whereas no isolate was found resistant to colistin. Multidrug resistant Acinetobacter baumannii was calculated to be 98.5%(n=68) in ICU isolates and was 83.11%(n=64) in non-ICU isolates. The percentage of XDR-Acinetobacter baumannii in ICU was 65.21%(n=45) and in non-ICU isolates was of 19.48% (n=15). Conclusion: Acinetobacter baumanni was identified as a common pathogen in the intensive care units infections with disappointing situation regarding antibiotic resistance. Keywords: Antibiotic susceptibility, Acinetobacter baumannii, Intensive care unit.